PENGARUH INVESTASI PEMERINTAH DAN INVESTASI SWASTA TERHADAP KESEMPATAN KERJA DAN PENGANGGURAN DI PROVINSI KALIMANTAN TIMUR The purpose of this study is to analyze the effect of foreign investment and domestic investment directly to employment opportuni - Syaihu, Akhmad Syaihu (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2012)
The purpose of this study is to analyze the effect of foreign investment and domestic investment directly to employment opportunities. To analyze the effect of foreign investment and domestic investment directly to unemployment. To analyze the effect of foreign investment and domestic investment indirectly to employment opportunities. To analyze the effect of foreign investment and domestic investment indirectly to unemployment. To analyze the effect of employment opportunities directly to unemployment. In order to test the hypothesis analysis the authors use analytical tools path analysis using SPSS 19. The data used in this study is the data per foreign investment, domestic investment, employment opportunities and unemployment in 2002-2011. The results show that two is a direct influence between foreign investment and domestic investment to employment opportunities and unemployment in East Kalimantan, and The results show that two is a indirect influence between foreign investment and domestic investment to employment opportunities and unemployment in East Kalimantan